2017
DOI: 10.1097/ncm.0000000000000253
|View full text |Cite
|
Sign up to set email alerts
|

Economic and Clinical Outcomes Resulting From the Stage 4 Chronic Kidney Disease Case Management Quality Improvement Initiative

Abstract: Purpose of Study:Chronic kidney disease (CKD) is a costly and burdensome public health concern. The goal of this study was to evaluate the impact on outcomes and utilization of a pilot program to identify and engage beneficiaries with CKD at risk for progression from Stage 4 to Stage 5.Primary Practice Settings:A quality improvement initiative was conducted to assess the impact of case management on costs and outcomes among 7,720 Cigna commercial medical beneficiaries with Stage 4 CKD enrolled in the United St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
1
2
0
1
Order By: Relevance
“…Our model uses demographics, comorbidities, and drug utilization data that are obtained routinely in patients with CKD in the enrollment, medical, and pharmacy claims databases, and the variables can be automatically generated and easily integrated into a clinical decision-making system. Similar to the systematic review studies discussed, 20–23 , 33 , 34 we found that younger age, male sex, advanced stage CKD, hypertension, DM, congestive heart failure, peripheral vascular disease, iron deficiency anemia, and higher prospective ERG risk score predict a higher risk of CKD progression to kidney failure. In addition, we found two new predictors; the presence of HK and poor RAASi adherence are significantly associated with progression of CKD.…”
Section: Discussionsupporting
confidence: 84%
“…Our model uses demographics, comorbidities, and drug utilization data that are obtained routinely in patients with CKD in the enrollment, medical, and pharmacy claims databases, and the variables can be automatically generated and easily integrated into a clinical decision-making system. Similar to the systematic review studies discussed, 20–23 , 33 , 34 we found that younger age, male sex, advanced stage CKD, hypertension, DM, congestive heart failure, peripheral vascular disease, iron deficiency anemia, and higher prospective ERG risk score predict a higher risk of CKD progression to kidney failure. In addition, we found two new predictors; the presence of HK and poor RAASi adherence are significantly associated with progression of CKD.…”
Section: Discussionsupporting
confidence: 84%
“…According to the National Kidney Foundation, in the United States, Medicare spends an average of 90,000 USD per patient per year on hemodialysis treatment for CKD [10]. Another study proved that performing AVF saved beneficiaries $199 per limb per month [11]. Yang.S et al in 2017 had reported in their study an average first-year cost per patient of USD 11,240 less for AVF than for SAVF [12].…”
Section: Introductionmentioning
confidence: 99%
“…Con respecto a la evidencia científica sobre los efectos de la GC se destacan: mejoras de la calidad de vida; aumento de la capacidad funcional; reducción de caídas, en personas mayores que viven en su domicilio; mejora en los resultados clínicos; disminución de complicaciones; aumento de satisfacción en pacientes y cuidadores; disminución de costos financieros en salud derivados de reducción de polifarmacia, de ingreso a instituciones de cuidado a largo plazo y hospitalizaciones; y, días de estancia y consultas de salud, en diferentes poblaciones (16)(17)(18).…”
Section: Resumo Introducciónunclassified